Determinants of defaulter to full vaccination among children aged 12-23 months in Siraro district, West Arsi zone, Oromia, Ethiopia: a case-control study - Ararso Hordofa Guye; Tadesse Nigussie; Mengistu Tesema; Dame Banti Shambi; Berhanu Senbeta Deriba; Negasa Shuma Dureso; Sisay Motuma Debela (BMC, 2023)
Abstract Background Vaccination is one of the most cost-effective global public health interventions to reduce childhood morbidity and mortality. Defaulters to full vaccination can put children at greater risk of acquiring vaccine-preventable disease outbreaks. The reason for not receiving full vaccination is not well explored, and hence, there is limited evidence about defaulters of vaccination in Ethiopia. Objectives To identify determinants of defaulter to full vaccination among children aged 12-23 months in Siraro District, West Arsi Zone, Oromia Region, Ethiopia. Methods A community-based unmatched case-control study was conducted among children aged 12-23 months from March 20 to April 30, 2022, with a total sample size of 444 (148 cases and 296 controls). Cases were children aged 12-23 months who had missed at least one routine vaccination dose, while controls were children who had received all of the recommended routine vaccinations. Consecutive sampling and simple random sampling techniques were used to select representative cases and controls respectively. Data were collected using a structured questionnaire, entered into Epi-data version 4.6, and exported to Statistical Package for Social Sciences version 26 for analysis. Logistic regression was used to identify determinants of the defaulter to full vaccination and the variables with p-value < 0.25 were recruited for multivariable analysis, and an adjusted odds ratio with a 95% confidence interval and a p-value of ≤ 0.05 was used to declare the statistical significance of the association. Result Of the assessed determinants of the defaulter to full vaccination; inadequate knowledge of mothers/caretakers (AOR = 4.32, 95% CI:2.78-6.70), educational status of a father unable to read and write (AOR = 3.66, 95% CI:1.29-10.39), time to reach health facility ≥ 30 minutes (AOR = 2.45, 95% CI:1.51-3.97), not told about the type of vaccine received (AOR = 2.37, 95% CI;1.27-4.45), no parents discussion on vaccination (AOR = 2.16, 95% CI:1.24-3.79), home delivery (AOR = 2.43, 95% CI:1.39-4.25) and not participated in pregnant mother conference (AOR = 2.47, 95% CI = 1.35-4.49) were the identified determinants of the defaulter to full vaccination. Conclusion Mother's' knowledge, father's education, place of delivery, time to reach a health facility, health workers who told the type of vaccine received, participation in pregnant mother conference, and parents' discussion on vaccination were the determinants of the defaulter to full vaccination status. Thus, the district health office should work on defaulters of vaccination by strengthening immunization service delivery and improving maternal knowledge on vaccination through pregnant mother conference participation.